Elements of Possessing and Controlling Narcotics Class I Not Plants Article 112 Paragraph (1) of Law Number 35 of 2009 Concerning Narcotics (Study of Lamongan District Court Decision Number: 221/Pid.Sus/2021/PN.Lmg) - Yanto, M.; Winarno, Jatmiko; Royani, Ahmad; Maftukhah, Fina Zuhrotun (Jurnal Independent, 2023)
AbstractThe state of Indonesia is a state of law. This is stated in Article 1 paragraph (3) of the Constitution of the Republic of Indonesia Year 1945 (hereinafter referred to as the 1945 Constitution) as a result of the Third Amendment to the 1945 Constitution. The State of the Republic of Indonesian a state of law respects and protects those who are suspected or suspected of committing criminal acts by granting rights to them in an effort to prove whether the person concerned is really a criminal offender or not. Based on the elements of possessing and mastering, it can be concluded that the element of possessing Article 112 paragraph (1) of Law No. 35 of 2009 can mean that the perpetrator illegally took the item (narcotics) to be used as his possession. While the element of "control" can mean that the perpetrator may not be a narcotics but can perform other actions that show the perpetrator really has power over the item. Based on the description, the public prosecution should be able to accommodate the provisions of Article 127 paragraph (1) of Law Number 35 of 2009, so that there is an alternative charge Third to entangle the Defendant with three alternative charges, namely First: Article 114 paragraph (1), Second: Article 112 paragraph (1), and Third Article 127 paragraph (1) of Law Number 35 of 2009.